2023
DOI: 10.1002/imhj.22046
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report measure of parental reflective functioning: A study of reliability and validity across three samples of varying clinical risk

Abstract: The Parental Reflective Functioning Questionnaire (PRFQ) provides an efficient way to measure a parent's capacity to recognize their child's mental states and to understand the relationship between underlying mental states and behavior. To date, limited work evaluates its psychometric properties beyond initial validation studies. Here we examined the reliability and validity of the PRFQ in three samples of varying clinical risk (e.g., community sample, previous mental health diagnosis, substance use disorder d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…This may be due to differences in the measurement of RF in this study, with all reports of RF by self‐report scales rather than the language‐based coding of measures like the PDI. Prior studies have reported differences in findings between the PRFQ and the PDI (Carlone et al., 2023). It may also be, as suggested by several studies in mothers, history of trauma alone does not predict RF, but instead the ability to mentalize about past trauma is associated with RF (Schechter et al., 2005; Stacks et al., 2014).…”
Section: Discussionmentioning
confidence: 91%
“…This may be due to differences in the measurement of RF in this study, with all reports of RF by self‐report scales rather than the language‐based coding of measures like the PDI. Prior studies have reported differences in findings between the PRFQ and the PDI (Carlone et al., 2023). It may also be, as suggested by several studies in mothers, history of trauma alone does not predict RF, but instead the ability to mentalize about past trauma is associated with RF (Schechter et al., 2005; Stacks et al., 2014).…”
Section: Discussionmentioning
confidence: 91%
“…The discrepancies between mothers’ PRF scores on the PRFQ and PDI may also reflect social desirability effects on self‐report measures (PRFQ) that interview measures (PDI) are more immune to. The question of changes in one measure of PRF versus the other is also complicated by recent work demonstrating minimal correlation between the PDI and PRFQ in several samples of mothers, including samples of mothers in substance use treatment (Carlone et al., 2023). Overall, however, our present findings raise important questions about why MIO showed diminished efficacy at improving mothers’ PRF when it was delivered by community‐based providers.…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of mediators and moderators of clinical outcomes will also undoubtedly inform the design of implementation‐effectiveness research done with larger samples (Curran et al., 2012). Given research being done on different approaches to the measurement of key constructs in parenting research (Carlone et al., 2023), additional work might also explore the utility of more economical, ecologically valid assessments of PRF, parenting behavior, and quality of the parent‐child relationship (e.g., parental embodied mentalizing, mind‐mindedness; Shai & Meins, 2018) rather than more expensive, time‐consuming measures that may not capture these phenomena occurring in more naturalistic settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses would have been more robust if RF were also coded from the PDI at baseline and tested as a covariate. Research documenting the limited correlation of RF measured by the PFRQ versus the PDI suggests that the PFRQ may not be a good proxy for the PDI (Anis et al., 2020; Carlone et al., 2023). Further, given that Latina mothers had lower PDI RF than non‐Latina mothers, we wonder whether a non‐linguistic measure of RF might be useful for assessing RF in this population in future studies to eliminate the possibility that any ethnic group differences were due to language proficiency.…”
Section: Discussionmentioning
confidence: 99%